SOCIO-PHILOSOPHICAL ANALYSIS OF THE CONCEPT OF "GRATITUDE" MENTIONED IN THE QURAN'S VERSES AND HADIS-SHARIFAH (Scientific journal of the Fergana State University, 2024)
This article provides a socio-philosophical analysis of the concept of "Gratitude" and its thoughts, presented in the verses of the Holy Quran and hadiths. It is also explained that gratitude helps a person to be patient and overcome their bad shortcomings.